(untitled) (Journal Of Educational and Psychological Researches, 2023)
Abstract: Inclusive education has experienced a number of positive educational trends and developments in many different countries, typically by recognising that all students, including those who have special educational needs (SEN), have a right to education. Inclusion of children with SEN in mainstream schools, alongside their peers, has become a major concern for interested educators, professionals and parents in many countries around the world. The reasons for this trend are due to a number of factors such as the increasing attention to the role of education in achieving social justice for pupils with SEN; the right of individuals with SEN to be educated along with their typically developing peers in mainstream schools; the benefit of equal opportunities for everyone in achieving self-growth and participating in building society (Al-Quraini, 2011). In terms of both policy and practice, inclusion has various interpretations. One of those interpretations defines inclusion as based on the belief that students with SEN can and should be educated in the same educational setting with typically developing peers, thus emphasising the importance of providing learning opportunities for all students (Ferguson, 2014). This paper aims to shed light on the nature of special education programs and the inclusion programs for people with disabilities in the Kingdom of Saudi Arabia by presenting and discussing policies and practices alike.